Travel mode choices in a greening market: the impact of electric vehicles and prior investments - Jeremy van Dijk; Mehdi Farsi; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
Through a choice experiment conducted among 995 Swiss respondents, we study the linkages between prior investment decisions and the choice of travel mode. Our experiment design and empirical framework aims to identify the impact of electric vehicles (EVs) and to test for two behavioural deviations from the rationally optimal usage. Prior investment in a car or public transport pass could be used ex-ante as a commitment device for overcoming self-control issues, or could affect mode choices ex-post through regret effects of sunk costs. We find no evidence to support the sunk cost hypothesis, but our findings provide partial evidence in favour of commitment mechanisms. A prior investment decision decreases the consumer's responsiveness to variation of travel time. However, such commitments do not seem to influence responses to changes in marginal travel cost. Further, we find that EV adoption does not result in a significant step-change in usage patterns above rational marginal cost reactions. Our results thus reinforce the importance of financial incentives in policies aiming at a behavioural change in travel mode choices.
Keywords: C25; C91; D01; D90; O33; Q40; Q55; 330; Transport; Behaviour; Choice experiment; Commitment; Sunk cost; Electric vehicles; Environmental policy